SOLUBILITY OPTIMIZATION OF TERBINAFINE HYDROCHLORIDE SOLID DISPERSION BY BINARY AND TERNARY METHOD - Zeeshan Masood; ujala mansoor; Ayesha Pervaiz; Maha Tariq; Husna Baqar; Zainab Naveed Khan; Aiman Baqar (International Journal of Pharmacy & Integrated Health Sciences, 2024)
Background: In the process of drug development, the most challenging factor is poor solubility. To formulate an oral dosage form, poor solubility and bioavailability are the main challenges. Objective: The objective of this research was to increase the solubility of terbinafine hydrochloride (TBF) by formulating binary and ternary solid dispersion (SD) by different techniques. Terbinafine hydrochloride is a BCS class II drug having low solubility, poor absorption and low bioavailability. Methodology: Physical mixture (PMSD), solvent evaporation (SESD), and kneading method (KMSD) were used to improve the solubility of TBF and prepare PMSD, SESD, KMSD and ternary solid dispersion (TSD) using PVPK30 and sodium lauryl sulphate (SLS) as hydrophilic polymer and surfactant. Nine formulations were designed to formulate binary SD by varying the ratios of TBF, PVPK30 and SLS (1:1, 1:3 and 1:5). Three formulations were prepared to form TSD with varying percentage of TBF with best formulation from binary SD (5%, 10% and 15%). Entire formulations were test for solubility studies, and a formulation that exhibit maximum increased solubility was selected to prepare binary and ternary SD of TBF. Every developed formulation was characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM) to observe chemical interactions, crystallinity and morphological changes, respectively. Results: The results show that binary SD and TSD has increased solubility in comparison with a pure drug. Although, TSD prepared using kneading method displayed the highest drug solubility (14.48 times) as compared to pure drug. Conclusion: The research determined that the solubility of TBF increased due to increased wettability, hydrophilicity of the carrier and reduced crystallinity.